Ultra-high gradient performance 3-Tesla MRI for super-fast and high-quality prostate imaging: initial experience - Leon M. Bischoff; Christoph Endler; Philipp Krausewitz; Joerg Ellinger; Niklas Klümper; Alexander Isaak; Narine Mesropyan; Dmitrij Kravchenko; Sebastian Nowak; Daniel Kuetting; Alois M. Sprinkart; Petra Mürtz; et al. (Insights into Imaging, 2024)
Abstract Objectives To implement and evaluate a super-fast and high-quality biparametric MRI (bpMRI) protocol for prostate imaging acquired at a new ultra-high gradient 3.0-T MRI system. Methods Participants with clinically suspected prostate cancer prospectively underwent a multiparametric MRI (mpMRI) on a new 3.0-T MRI scanner (maximum gradient strength: 200 mT/m, maximum slew rate: 200 T/m/s). The bpMRI protocol was extracted from the full mpMRI protocol, including axial T2-weighted and diffusion-weighted (DWI) sequences (b0/800, b1500). Overall image quality was rated by two readers on a five-point Likert scale from (1) non-diagnostic to (5) excellent. PI-RADS 2.1 scores were assessed by three readers separately for the bpMRI and mpMRI protocols. Cohen’s and Fleiss’ κ were calculated for PI-RADS agreement between protocols and interrater reliability between readers, respectively. Results Seventy-seven male participants (mean age, 66 ± 8 years) were included. Acquisition time of the bpMRI protocol was reduced by 62% (bpMRI: 5 min, 33 ± 21 s; mpMRI: 14 min, 50 ± 42 s). The bpMRI protocol showed excellent overall image quality for both the T2-weighted (median score both readers: 5 [IQR: 4–5]) and DWI (b1500) sequence (median score reader 1: 4 [IQR: 4–5]; reader 2: 4 [IQR: 4–4]). PI-RADS score agreement between protocols was excellent (Cohen’s κ range: 0.91–0.95 [95% CI: 0.89, 0.99]) with an overall good interrater reliability (Fleiss’ κ, 0.86 [95% CI: 0.80, 0.92]). Conclusion Ultra-high gradient MRI allows the establishment of a high-quality and rapidly acquired bpMRI with high PI-RADS agreement to a full mpMRI protocol. Trials registration Clinicaltrials.gov, NCT06244680, Registered 06 February 2024, retrospectively registered, https://classic.clinicaltrials.gov/ct2/show/NCT06244680 . Critical relevance statement A novel 3.0-Tesla MRI system with an ultra-high gradient performance enabled high-quality biparametric prostate MRI in 5.5 min while achieving excellent PI-RADS agreement with a standard multiparametric protocol. Key Points Multi- and biparametric prostate MRIs were prospectively acquired utilizing a maximum gradient of 200 mT/m. Super-fast biparametric MRIs showed excellent image quality and had high PI-RADS agreement with multiparametric MRIs. Implementation of high gradient MRI in clinical routine allows accelerated and high-quality biparametric prostate examinations. Graphical Abstract